Leadership in Action : a Question of Leadership - Should Managers be Able to Review the Ratings Their Subordinates Receive from 360-Degree Feedback Instruments? - McCauley, Sylvester Taylor. Cindy (Center for Creative Leadership, 2003)
Confidentiality is a core element of an effective approach to developmental feedback, yet managers would be foolish to rely only on their own assessments in making administrative decisions.